Prison and probation - Pleško, Martina (Varstvoslovje, 2026)
Purpose: The aim of the paper is to analyse dominant media narratives and differences with respect to the visibility and interpretation of prison sentences and probation in Croatian media. Design/Methods/Approach: Content analysis of articles published in leading Croatian online media between 2020 and 2024 was conducted using a mixed-methods approach. The analysis focused on the thematic framework, language, frequency of mentions, and social context. Findings: The topic of prison sentences was mentioned significantly more often than probation was. Regarding their portrayals, certain differences were found in the tone of the articles, the use of sensationalism, the naming of well-known persons or the full identity of offenders, suspects, convicts, prisoners and victims, as well as in the use of cover images. Research Limitations/Implications: The research has several limitations, including the method used to search for articles and the possible influence of the researcher’s subjectivity and bias in the analysis. Future research should include more websites over a longer period and examine journalists’ reporting methods and their familiarity with criminal sanctions. Practical Implications: The findings may assist with a better understanding of how the media shape public perceptions of prison sentences and probation, and open up space for a discussion on the visibility and acceptance of different forms of sanctions in Croatian society. Originality/Value: As the first research of its kind in Croatia, this work can help raise awareness and understanding of how the media portray criminal sanctions, while also serving as a starting point for comparative analysis of the media representation of criminal sanctions on an international level.
Keywords: community sanctions; Croatia; Hrvaška; media; mediji; prison sentence; probacija; probation; sanctions; sankcije; skupnostne sankcije; zaporna kazen